Managing Organizational Inertia: Indonesian Family Business Perspective - Teofilus, Teofilus; Ardyan, Elia; Sutrisno, Timotius F. C. W.; Sabar, Sabar; Sutanto, Verrell (Frontiers in Psychology, 2022)
The ability to transform on a regular basis is critical in the effort to adapt to external challenges; however, changes to an organization’s fundamental characteristics may increase the likelihood of failure. Because of this, organizational restructuring efforts appear to engender cynicism, which appears to be one of the most significant obstacles facing contemporary businesses, particularly in this area. Organizational inertia is the term used to describe this aversion to change, as well as the desire to maintain the current status quo. A new organizational culture capable of combating the incidence of organizational stagnation is required by massive social, economic, and technological difficulties, and firms that employ the concept of empowering leadership will be able to meet these challenges. For the purposes of this study, a framework for discussing the phenomena of organizational cynicism was developed and implemented.